BUILDING MULTI-FACTOR AUTHENTICATION PROVIDER USING ASP.NET - AAdith Prasetya; Anggi Wijaya; Moehammad Radif; Agus Kurniawan (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2010)
In this paper, we present an authentication system which can be served as multi-factor authentication provider.This system has supported various authentication methods (ASP Membership, OpenID, and SMS one-timepassword) in either standard one-factor or multi-factor authentication method. It has been tested with twoconsumer websites (MOSS 2007 website and ASP .NET MVC website) in either standard XML post or DiffieHellman protocol. This system was developed as a solution for user’s multi-account in multiple websitesproblem.Keywords: Diffie Hellman, Multi-factor Authentication, OpenID